The prospect of orally administered monoclonal secretory IgA (SIgA) antibodies to prevent enteric bacterial infections - Angelene Richards; Danielle Baranova; Nicholas J. Mantis (Taylor & Francis Group, 2022)
Eliminating diarrheal diseases as a leading cause of childhood morbidity and mortality in low- and middle-income countries (LMICs) will require multiple intervention strategies. In this review, we spotlight a series of preclinical studies investigating the potential of orally administered monoclonal secretory IgA (SIgA) antibodies (MAbs) to reduce disease associated with three enteric bacterial pathogens: Campylobacter jejuni, enterotoxigenic Escherichia coli (ETEC), and invasive Salmonella enterica serovar Typhimurium. IgA MAbs targeting bacterial surface antigens (flagella, adhesins, and lipopolysaccharide) were generated from mice, humanized mice, and human tonsillar B cells. Recombinant SIgA1 and/or SIgA2 derivates of those MAbs were purified from supernatants following transient transfection of 293 cells with plasmids encoding antibody heavy and light chains, J-chain, and secretory component (SC). When administered to mice by gavage immediately prior to (or admixed with) the bacterial challenge, SIgA MAbs reduced infection C. jejuni, ETEC, and S. Typhimurium infections. Fv-matched IgG1 MAbs by comparison were largely ineffective against C. jejuni and S. Typhimurium under the same conditions, although they were partially effective against ETEC. While these findings highlight future applications of orally administered SIgA, the studies also underscored the fundamental challenges associated with using MAbs as prophylactic tools against enteric bacterial diseases.